(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The work provides detailed explanations of the history of the discovery of radioactivity and X-rays, ways to study the phenomenon of nuclear explosions using interactive methods, and its scientific novelty is that in order to form students’ competencies in teaching the topic, the "Brainstorming" method was used to determine the results of the organized training session. The results showed that the method increased students’ interest in the lesson and strengthened their memory.